Sulfonated polybenzimidazole proton exchange membrane as well as preparation method and application thereof
By designing and preparing the sulfonated polybenzimidazole proton exchange membrane, the problem of difficult balance of conductivity and ion selectivity in all vanadium flow batteries is solved, the cycle stability and energy efficiency of the battery are improved, and the cost and environmental impact are reduced.
Patent Information
- Application Number
- CN202411926403.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-03-18
AI Technical Summary
All-vana flow batteries have problems such as cross-permeability of positive and negative electrode vanadium ion electrolyte, low capacity attenuation and energy conversion efficiency, and the high cost and ecological environment of Nafion membranes are greatly affected.
A sulfonated polybenzimidazole proton exchange membrane is designed and prepared. The membrane structure includes a polybenzimidazole polymer backbone and sulfonic acid group. The conductivity and ion selectivity of the membrane are enhanced by synthesis of a high free volume polybenzimidazole polymer backbone and sulfonation treatment.
The cycle stability and energy efficiency of all vanadium flow batteries are improved, the production cost of membrane materials and the initial installation cost of batteries are reduced, and the impact on the ecological environment is reduced.
Smart Images

Figure CN119650784A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of all-vanadium liquid flow batteries, and in particular to a sulfonated polybenzimidazole proton exchange membrane and a preparation method and application thereof. Background Art
[0002] Promoting the decarbonization of the global energy system is crucial to achieving sustainable social and economic development and effectively mitigating the impact of climate change. So far, China's installed capacity of wind and photovoltaic new energy has reached 1.2 billion kWh, but its power generation accounts for only 5% of the total power generation. In order to achieve the "dual carbon" goal, the proportion of thermal power generation should be reduced to less than 10%, and the power generation of new energy must be increased to more than 60%. The installed capacity of new energy will continue to grow significantly in the future. However, wind and photovoltaic new energy have the disadvantages of intermittent, seasonal and volatile, which makes it impossible to directly connect to the power grid, resulting in serious wind and light abandonment. Therefore, it is urgent to equip it with matching energy storage technology. Liquid flow batteries are considered to be the preferred technical route for the development of energy storage technology due to their inherent safety, simple expansion and high flexibility.
[0003] At present, all-vanadium liquid flow battery is the most mature liquid flow battery technology because it has advantages such as high energy conversion efficiency and high power density. However, the high cost and maintenance cost of all-vanadium liquid flow battery limit its large-scale application. The cost of all-vanadium liquid flow battery is as high as 2.1 yuan / Wh, which is three times that of lithium battery (0.7 yuan / Wh), of which the cost of proton exchange membrane accounts for 30% of the total cost. At present, all-vanadium liquid flow battery generally uses Nafion membrane as proton exchange membrane because of its high chemical stability and high ionic conductivity. However, the ion selectivity of Nafion membrane is poor, resulting in low coulomb conversion efficiency of all-vanadium liquid flow battery assembled by Nafion membrane, which is easy to decay, greatly increasing the maintenance cost of all-vanadium liquid flow battery. Moreover, Nafion membrane is manufactured by DuPont in the United States, and the unit price of Nafion membrane is as high as US$1,000 / m 2 The most important thing is that the preparation of Nafion membrane involves fluorine chemical industry, and the large-scale use of Nafion membrane will inevitably cause great damage to the ecological environment.
[0004] Polybenzimidazole membranes have excellent ion selectivity and low preparation and production costs under acidic conditions, but their poor proton conductivity limits their application in vanadium flow batteries. Therefore, designing and studying polybenzimidazole membrane materials with high ion selectivity and high ion conductivity will break through the problems of low energy conversion efficiency and large capacity attenuation of all-vanadium flow batteries. Most importantly, the cost of all-vanadium flow batteries can be greatly reduced through membrane material modification. Summary of the invention
[0005] In view of the problems in the prior art of cross-permeation of vanadium ion electrolyte between the positive and negative electrodes of all-vanadium liquid flow batteries, capacity attenuation and low energy conversion efficiency of all-vanadium liquid flow batteries, the purpose of the present invention is to provide a sulfonated polybenzimidazole proton exchange membrane and a preparation method and application thereof, so as to solve the problem of difficulty in balancing conductivity and ion selectivity in the related technology.
[0006] In order to achieve the above purpose, the technical solution adopted by the present invention is:
[0007] A sulfonated polybenzimidazole proton exchange membrane, the proton exchange membrane structure comprises a polymer main chain and a sulfonic acid group, as shown in formula (I);
[0008]
[0009] The polymer main chain is a polybenzimidazole polymer or a derivative thereof, and the monomer A is one of the above A1 to A5.
[0010] The sulfonated polybenzimidazole proton exchange membrane has an ion exchange capacity of 0.5-3.5 meq / g, a sulfonation degree of 40%-100%, and an ion exchange capacity of 1.2-2.9 meq / g.
[0011] The method for preparing the sulfonated polybenzimidazole proton exchange membrane comprises the following steps:
[0012] S1. polymerizing monomer A and 3,3'-diaminobenzidine under polyphosphoric acid catalysis to obtain a polymer backbone;
[0013] S2. The polymer main chain obtained in step S1 is dissolved in concentrated sulfuric acid for sulfonation treatment. After treatment at a set temperature for a set time, the polymer main chain is taken out, washed with deionized water and dried to obtain a sulfonated polybenzimidazole polymer.
[0014] In the method for preparing the sulfonated polybenzimidazole proton exchange membrane, in step S1, the polymerization reaction temperature is 140° C. to 250° C., and the polymerization reaction time is 2 h to 96 h.
[0015] In the method for preparing the sulfonated polybenzimidazole proton exchange membrane, in step S1, the mass ratio of monomer A, 3,3'-diaminobenzidine and polyphosphoric acid is 1:1-2:20-100.
[0016] In the method for preparing the sulfonated polybenzimidazole proton exchange membrane, in step S2, the temperature of the sulfonation treatment is 60° C. to 120° C., and the time of the sulfonation treatment is 4 h to 24 h.
[0017] In the method for preparing the sulfonated polybenzimidazole proton exchange membrane, in step S2, the mass ratio of the polymer main chain to concentrated sulfuric acid is 1:5-20.
[0018] The application of the sulfonated polybenzimidazole proton exchange membrane is used as a proton exchange membrane of an all-vanadium liquid flow battery.
[0019] The application of the sulfonated polybenzimidazole proton exchange membrane, the positive electrode electrolyte of the all-vanadium liquid flow battery is a solution containing tetravalent vanadium ions and pentavalent vanadium ions, the negative electrode electrolyte is a solution containing divalent vanadium ions and trivalent vanadium ions, the supporting electrolyte is one or more of sulfuric acid, hydrochloric acid or phosphoric acid, and the molar concentration ratio of the positive electrode electrolyte to the negative electrode electrolyte is 1:1 to 2:1; the bipolar plate of the all-vanadium liquid flow battery is a graphite bipolar plate, and the current collector of the all-vanadium liquid flow battery is one of carbon cloth and graphite carbon felt.
[0020] The design idea of the present invention is:
[0021] The present invention designs and prepares a sulfonated polybenzimidazole proton exchange membrane, wherein the proton exchange membrane structure includes a polybenzimidazole polymer main chain and a sulfonic acid group, and the free volume of the polybenzimidazole polymer is regulated by synthesizing raw materials of different structures, and the polybenzimidazole polymer is sulfonated to obtain the polybenzimidazole proton exchange membrane. The present invention selects raw materials with high rigidity and high free volume to construct the polybenzimidazole polymer main chain, and improves the mechanical properties of the polybenzimidazole membrane while constructing a fast ion channel in the polymer membrane. The free volume of the polybenzimidazole membrane is increased by main chain structure design, and a proton transfer channel is constructed to reduce mass transfer resistance, and the increased free volume can accommodate water molecules to limit the swelling of the membrane material. The hydrophilicity of the polybenzimidazole membrane is further increased by sulfonation treatment, and the proton transfer rate is further improved.
[0022] The advantages and beneficial effects brought by the technical solution provided by the present invention are as follows:
[0023] The present invention provides a method for preparing a sulfonated polybenzimidazole proton exchange membrane, thereby obtaining a proton exchange membrane suitable for an all-vanadium liquid flow battery, improving the conductivity and ion selectivity of the proton exchange membrane, improving the cycle stability and energy efficiency of the all-vanadium liquid flow battery, and reducing the production and preparation of membrane materials and the initial installation cost of the all-vanadium liquid flow battery.
[0024] The proton exchange membrane comprises a large amount of imidazole groups, and under acidic conditions, the imidazole groups can combine hydrogen ions to form quaternary ammonium salts (positively charged) to repel vanadium ions. The high free volume raw materials selected can limit the spatial conformation of the molecular chain after the synthesis of the polybenzimidazole polymer skeleton, increase the free volume of the molecular chain, increase the molecular chain spacing, thereby realizing the construction of the proton transport channel, and further accelerating the proton conduction by introducing sulfonic acid groups on the polymer backbone. Meanwhile, the free volume increased by the polymer molecular chain can accommodate the swelling of the water molecule limiting membrane material. In addition, the polybenzimidazole membrane material raw material cost is low, the synthesis is simple, the chemical property is stable, can be repeatedly utilized, and the operation and maintenance cost is low, with obvious cost advantage.
[0025] At the same time, the all-vanadium liquid flow battery is an aqueous battery with extremely high safety. The prepared electrolyte can be recycled for many times and is environmentally friendly. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is the performance diagram of the 500-cycle all-vanadium liquid flow battery of Example 5.
[0027] Figure 2 This is the performance diagram of the 100-cycle all-vanadium liquid flow battery of Comparative Example 1. DETAILED DESCRIPTION
[0028] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0029] In the embodiments of the present invention, all are configured to correspond to flow batteries, and the test parameters and equipment refer to the contents recorded in "NBT 42081-2016 All-vanadium flow battery single cell performance test method", and the test environment and steps are as follows:
[0030] Test environment:
[0031] ——Ambient temperature: 20℃±5℃;
[0032] ——Air humidity: 50%±5%;
[0033] ——Electrolyte temperature: 30℃±5℃.
[0034] Test steps:
[0035] a) The battery system is charged to 90% SOC;
[0036] b) The battery system is operated at a current density of 200 mA / cm 2 Discharging until the discharge cut-off voltage;
[0037] c) The battery system is operated at a current density of 200 mA / cm 2 Charging is performed until the charging cut-off voltage;
[0038] d) The battery system is operated at a current density of 200 mA / cm 2 Discharging until the discharge cut-off voltage;
[0039] e) repeat steps c) to d);
[0040] f) Record various parameters of each charge and discharge cycle;
[0041] g) The average coulombic efficiency, voltage efficiency and energy efficiency of the all-vanadium liquid flow battery are the average values of the data after multiple cycles.
[0042] Example 1
[0043] In this embodiment, a method for preparing a proton exchange membrane for an all-vanadium liquid flow battery is as follows:
[0044] 1. The selected proton exchange membrane is as follows:
[0045]
[0046] S1. Dissolve terephthalic acid and 3,3'-diaminobenzidine in polyphosphoric acid, and stir at 160° C. for 3 hours to obtain a viscous polymer as the polymer main chain. The mass ratio of terephthalic acid, 3,3'-diaminobenzidine and polyphosphoric acid is 1:1.5:50.
[0047] S2. Dissolve the polymer main chain obtained in step S1 in concentrated sulfuric acid (98 wt%), and stir at 100° C. for 5 h to obtain a sulfonated polybenzimidazole polymer, wherein the mass ratio of the polymer main chain to the concentrated sulfuric acid is 1:10.
[0048] In this embodiment, the thickness of the proton exchange membrane is 35 μm, the degree of sulfonation of the proton exchange membrane is 70%, and the ion exchange capacity of the proton exchange membrane is 2.1 meq / g.
[0049] 2. The configuration of the all-vanadium liquid flow battery is as follows:
[0050] Negative electrode: 1.6 mol / L solution of divalent vanadium ions and trivalent vanadium ions, the balance is water;
[0051] Positive electrode: 1.6 mol / L solution of 4-valent vanadium ions and 5-valent vanadium ions, the balance is water;
[0052] The flow battery is a single cell, wherein the bipolar plate is a graphite electrode, the current collector is a graphite carbon felt, and the sulfonated polybenzimidazole proton exchange membrane obtained in this embodiment is used. The storage tank of the flow battery uses two 0.1L transparent bottles, and a peristaltic pump is used between the storage tank and the battery stack as a power source. The volume of the negative electrode electrolyte is 0.1L, and the volume of the positive electrode electrolyte is 0.1L.
[0053] Example 2
[0054] The difference from Example 1 is that the selected proton exchange membrane is as follows:
[0055]
[0056] The preparation of the proton exchange membrane, the configuration of the positive and negative electrolytes, and the configuration of the flow battery are the same as those in Example 1.
[0057] Example 3
[0058] The difference from Example 1 is that the selected proton exchange membrane is as follows:
[0059]
[0060] The preparation of the proton exchange membrane, the configuration of the positive and negative electrolytes, and the configuration of the flow battery are the same as those in Example 1.
[0061] Example 4
[0062] The difference from Example 1 is that the selected proton exchange membrane is as follows:
[0063]
[0064] The preparation of the proton exchange membrane, the configuration of the positive and negative electrolytes, and the configuration of the flow battery are the same as those in Example 1.
[0065] Example 5
[0066] The difference from Example 1 is that the selected proton exchange membrane is as follows:
[0067]
[0068] The preparation of the proton exchange membrane, the configuration of the positive and negative electrolytes, and the configuration of the flow battery are the same as those in Example 1.
[0069] Table 1 Flow battery test table
[0070] Coulombic efficiency % Voltage efficiency % Energy efficiency % Capacity retention rate % Example 1 99.53% 80.25% 79.87% 75.33% Example 2 99.67% 80.27% 80.0% 76.25% Example 3 99.48% 79.25% 78.83% 73.21% Example 4 99.47% 79.46% 79.03% 75.45% Example 5 99.65% 80.55% 80.26% 77.27%
[0071] like Figure 1As shown, the all-vanadium liquid flow battery of Example 5 was subjected to 500 cycles of charge and discharge cycle test. From the above experiment, it can be seen that the all-vanadium liquid flow battery assembled with sulfonated polybenzimidazole proton exchange membrane synthesized from anthracene-2,6-dicarboxylic acid exhibits good cycle stability and capacity retention rate. The experimental results of Examples 1 to 5 are similar to Figure 1 , the coulombic efficiency is 99.47%~99.65%, the voltage efficiency is 79.25%~80.55%, the energy efficiency is 78.83%~80.26%, and the capacity retention rate is 73.21%~77.27%. From the specific experimental data, it can be seen that the polybenzimidazole proton exchange membrane battery with a stronger rigid molecular structure has better performance.
[0072] Comparative Example 1
[0073] The difference from Example 1 is that the comparative example is an all-vanadium liquid flow battery, which is configured as follows:
[0074] Membrane material: Nafion 212;
[0075] Negative electrode: 1.6 mol / L solution of divalent vanadium ions and trivalent vanadium ions, the remainder is water, the volume is 0.1L.
[0076] Positive electrode: 1.6 mol / L solution of tetravalent vanadium ions and pentavalent vanadium ions, the remainder being water, with a volume of 0.1 L.
[0077] After assembly is completed, the battery cycle performance test is carried out according to the above test conditions. Figure 2 As shown, after 100 cycles of charge and discharge cycle testing, the capacity retention rate of the battery is greatly attenuated, with a decay rate of about 40%, a coulombic efficiency of 96.21%, an energy efficiency of 75.24%, and a voltage efficiency of 78.21%.
[0078] It can be seen from the above experimental results that the sulfonated polybenzimidazole proton exchange membrane provided by the present invention greatly improves the stability and capacity retention rate of the all-vanadium redox flow battery.
[0079] The experimental results show that the present invention designs and prepares a sulfonated polybenzimidazole proton exchange membrane. By selecting high-rigidity and high-free-volume synthetic monomers, a high-free-volume polybenzimidazole polymer skeleton is constructed to construct a proton transfer channel, while limiting the swelling of the membrane material. The proton transfer capacity is further improved by introducing sulfonic acid groups. While ensuring high ion selectivity, the conductivity of the sulfonated polybenzimidazole proton exchange membrane is improved, the crossover of the positive and negative active substances of the all-vanadium liquid flow battery is suppressed, and the capacity attenuation and low energy efficiency of the all-vanadium liquid flow battery are improved. After 500 charge and discharge cycles, the all-vanadium liquid flow battery using this series of proton exchange membranes maintains a high energy efficiency and capacity retention rate, and the long-term cycle stability is improved by 100%.
[0080] The above description of the present invention only provides some specific embodiments for those skilled in the art to facilitate understanding and implementation. For these embodiments, those skilled in the art may make a variety of obvious improvements, and the basic principles defined in the present invention may be applied in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention should not be limited to the embodiments shown in the present invention document, and other changes and modifications to the present invention without departing from the spirit and scope of the present invention should be covered by the claims of the present invention.
Claims
1. A sulfonated polybenzimidazole proton exchange membrane, characterized in that: The proton exchange membrane structure includes a polymer main chain and a sulfonic acid group, as shown in formula (I); The polymer main chain is a polybenzimidazole polymer or a derivative thereof, and the monomer A is one of the above A1 to A5.
2. The sulfonated polybenzimidazole proton exchange membrane according to claim 1, characterized in that: The proton exchange membrane has an ion exchange capacity of 0.5 to 3.5 meq / g, a sulfonation degree of 40% to 100%, and an ion exchange capacity of 1.2 to 2.9 meq / g.
3. A method for preparing a sulfonated polybenzimidazole proton exchange membrane according to claim 1 or 2, characterized in that: The following steps are involved: S1. polymerizing monomer A and 3,3'-diaminobenzidine under polyphosphoric acid catalysis to obtain a polymer backbone; S2. The polymer main chain obtained in step S1 is dissolved in concentrated sulfuric acid for sulfonation treatment. After treatment at a set temperature for a set time, the polymer main chain is taken out, washed with deionized water and dried to obtain a sulfonated polybenzimidazole polymer.
4. The method for preparing the sulfonated polybenzimidazole proton exchange membrane according to claim 3, characterized in that: In step S1, the polymerization reaction temperature is 140° C. to 250° C., and the polymerization reaction time is 2 h to 96 h.
5. The method for preparing the sulfonated polybenzimidazole proton exchange membrane according to claim 3, characterized in that: In step S1, the mass ratio of monomer A, 3,3'-diaminobenzidine and polyphosphoric acid is 1:1-2:20-100.
6. The method for preparing the sulfonated polybenzimidazole proton exchange membrane according to claim 3, characterized in that: In step S2, the temperature of the sulfonation treatment is 60°C to 120°C, and the time of the sulfonation treatment is 4h to 24h.
7. The method for preparing the sulfonated polybenzimidazole proton exchange membrane according to claim 3, characterized in that: In step S2, the mass ratio of the polymer main chain to concentrated sulfuric acid is 1:5-20.
8. An application of the sulfonated polybenzimidazole proton exchange membrane according to claim 1 or 2, characterized in that: The proton exchange membrane is used as a proton exchange membrane of an all-vanadium liquid flow battery.
9. The use of the sulfonated polybenzimidazole proton exchange membrane according to claim 8, characterized in that: The positive electrode electrolyte of the all-vanadium liquid flow battery is a solution containing tetravalent vanadium ions and pentavalent vanadium ions, the negative electrode electrolyte is a solution containing divalent vanadium ions and trivalent vanadium ions, the supporting electrolyte is one or more of sulfuric acid, hydrochloric acid or phosphoric acid, and the molar concentration ratio of the positive electrode electrolyte to the negative electrode electrolyte is 1:1 to 2:1; the bipolar plates of the all-vanadium liquid flow battery are graphite bipolar plates, and the current collector of the all-vanadium liquid flow battery is one of carbon cloth and graphite carbon felt.
Citation Information
Cited By
Microporous sulfonated polybenzimidazole proton exchange membrane for all-vanadium redox flow battery as well as preparation method and application of microporous sulfonated polybenzimidazole proton exchange membrane
CN120149471A
A microporous sulfonated polybenzimidazole proton exchange membrane for all-vanadium redox flow battery and its preparation method and application
CN120149471B
High-oxidation-resistance polybenzimidazole proton exchange membrane as well as preparation method and application thereof
CN121378746A
A high-oxidation-resistance polybenzimidazole proton exchange membrane, a preparation method and application thereof
CN121378746B